Integrating e-learning in teacher education - Agalo, Joyce (JFP Publishers, 2021)
In considering the integration of electronic learning (e-learning) in teacher education, there is also a need to consider the kinds of skills and competencies the teacher needs for using such technical media in pedagogical activities in a teaching classroom. Such competencies will enable the teacher to guide the learners in encoding and decoding messages. It is also important that the teachers acquire various forms of knowledge and background assumptions about the relevance of the use of technology in pedagogical practice. This paper covers the e-learning issues of both the teacher and the learner. It gives a brief history of distance learning to include e-learning and teacher competencies in the utilization of related technology used in e-learning delivery modes. It also discusses how important e-learning is in the current society where technological knowhow is advancing.
Keywords: Curriculum; Distance education; Education; E-Learning; Teacher; Teacher education